أثر التعديل الدستوري لسنة 2020 على تطور المجلس الوطني الاقتصادي والاجتماعي والبيئي - مريخي، سامي; معمري، نصر الدين Maamari, Nasruldin (المركز الجامعي المقاوم الشيخ آمود بن مختار إيليزي, 2022)
تهدف الدراسة إلى إبراز المكانة الحقيقية التي يحتلها المجلس الوطني الاقتصادي والاجتماعي والبيئي في ظل التعديل الدستوري لسنة 2020 بما له من صلاحيات فعلية وصورية، وتبيان حدود الضوابط والقيود المفروضة على استشارته، بالإضافة إلى تحليل كيفية تسيير المجلس وخصوصية تركيبته البشرية، مع إبراز دوره ومساهمته في صنع القرار السياسي والإداري. وقد خلصت الدراسة إلى أن المجلس الوطني الاقتصادي والاجتماعي والبيئي مؤسسة في غاية الأهمية والفاعلية من خلال المساهمة التي يقدمها للسلطات العمومية في عملية اتخاذ القرارات، إلا أنه يبقى كغيره من الهيئات الاستشارية الأخرى في الجزائر لا تأخذ الاستشارة فيه صورة الإلزام وهذا ما يؤدي إلى التقليص من فاعليته، وبالتالي لا يستطيع هذا الأخير القيام بدوره على أكمل وجه. Study aims to highlight the real position occupied by the National Economic, Social and Environmental Council in light of the constitutional amendment of 2020 With what he has of real and fictitious powers, and to indicate the limits of controls and restrictions imposed on its consultation, in addition to analyzing how the Council runs and the specificity of its human structure, highlighting its role and contribution in political and administrative decision-making. The study concluded that the National Economic, Social and Environmental Council is a very important and effective institution through the contribution it makes to the public authorities in the decision-making process, However, it remains like other advisory bodies in Algeria, that the consultation does not take the form of binding, and this leads to reducing the effectiveness of this council, and therefore the latter cannot perform its role to the fullest.
Keywords: القانون الجزائري -- التعديل الدستوري -- المؤسسات الاستشارية